Indications and diagnosis‐specific features of maternal and neonatal peripartum intensive care unit admissions: A retrospective study. Issue 2 (2nd December 2021) - Taube, Hamutal S.; Matot, Idit; Levy, Nadav; Goren, Or; Marom, Ronella; Weiniger, Carolyn F.
Abstract: Background: Although peripartum intensive care unit admission indications are well‐reported, clinical and laboratory details rarely are. We described admission indications and categorised laboratory values and vital signs according to admission diagnosis. Methods: Retrospective Institutional Review Board approved study. We identified intensive care unit admission diagnosis, laboratory values and vital signs from patient charts. Groups were compared according to admission diagnoses. Data were analysed using descriptive statistics. Results: We included 91 general intensive care unit admissions among 56, 865 deliveries (2011–2015) with complete data. The most common admission diagnosis was postpartum haemorrhage followed by hypertensive diseases of pregnancy and respiratory complications. Women with postpartum haemorrhage had lower mean (standard deviation) platelet counts (120.2 (45.8) vs. 181.2 (109.9), p = .003) and temperatures (35.7 (1.1) vs. 36.5 (1.2), p = .002). Women with hypertensive diseases of pregnancy had higher mean (standard deviation) blood pressures (systolic 150.4 (29.1) vs. 127.4 (21.0), p = .013, diastolic 100.3 (18.7) vs. 76.1 (16.1), p = .001), creatinine (1.1 (0.6) vs. 0.8 (0.3), p = .003), urea (14.6 (7.7) vs. 10.5 (4.7), p = .005) and liver enzymes, including aspartate transaminase (258.4 (297.0) vs. 41.4 (42.9), p = .000), alanine transaminase (184.4 (199.2) vs. 35.1 (75.9), p = .000), and alkaline phosphatase (166.6 (112.6) vs. 96.0 (60.0), p = .006). Women with respiratory complications had lower mean (standard deviation) oxygen saturations (93.7 (6.1) vs. 98.0 (2.6), p = .000), and higher mean (standard deviation) temperatures (37.1 (0.8) vs. 36.0 (1.2), p = .001). Conclusions: We report differences in laboratory values and vital signs, according to intensive care unit admission diagnosis. Recognising these differences might help individualise patient assessment and care.